E-091 Stroke Awareness Knowledge Gap in Women. (22nd July 2019) - Campos, J; Lin, P; Wang, L; NassimiMoghaddam, K; Do, F; Lee, J; Imbre, N; Totounji, I; Strebig, D; Kim, J; Golshani, K; Lin, L
Abstract : Introduction: Understanding current levels of stroke awareness in women may highlight knowledge gaps and areas for targeted education in those most likely to be affected by stroke. The purpose of this study was to evaluate awareness of stroke (i.e. stroke symptoms and risk factors) among women in Orange County. Following baseline assessments in knowledge, educational programs will be implemented as a public health intervention to raise awareness. Methods: An institutional IRB-approved, prospectively collected survey study was conducted among randomly selected English-speaking women, age 18–82 years, throughout a variety of public locations in Orange County, California, between October 2018 to March 2019. Knowledge of stroke awareness was assessed by 6 standardized open-ended questions. Results: A total of 672 women, average age 40.6±16 years, responded to the survey. The majority of the participants knew someone who had experienced a stroke, 67.6% (n=454), yet 30.1% (n=202) of participants were aware of the two types of stroke, ischemic and hemorrhagic. Of the 21% (n=141) who correctly identified modifiable lifestyle factors to decrease the risk for stroke, the majority correctly answered blood pressure control. While, 17.4% (n=117) correctly identified the constellation of common signs and symptoms of stroke, the majority correctly answered slurred speech. Among the age group at highest risk for stroke (>65 years), particular knowledge deficits in the benefits of smoking cessation and adequate diabetes management to decrease stroke risk. Conclusions: These preliminary study results indicate a potential and significant lack of women's knowledge of stroke awareness in the Orange County area, despite a majority of survey respondents having a close connection to a stroke patient. Continuation of this project will provide further information on the current knowledge gaps in stroke awareness and highlight concepts for targeted education for those women at greatest risk of stroke. Tables 1–3, All values are percentages of respondents within the respective age group. Disclosures: J. Campos: None. P. Lin: None. L. Wang: None. K. NassimiMoghaddam: None. F. Do: None. J. Lee: None. N. Imbre: None. I. Totounji: None. D. Strebig: None. J. Kim: None. K. Golshani: None. L. Lin: 1; C; Stryker. 2; C; Medtronic, MicroVention.